2022
DOI: 10.1029/2021jg006748
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Forest Complexity: Resource Use Efficiency, Disturbance, and the Structure‐Function Relationship

Abstract: Structurally complex forests optimize resources to assimilate carbon more effectively, leading to higher productivity. Information obtained from Light Detection and Ranging (LiDAR)‐derived canopy structural complexity (CSC) metrics across spatial scales serves as a powerful indicator of ecosystem‐scale functions such as gross primary productivity (GPP). However, our understanding of mechanistic links between forest structure and function, and the impact of disturbance on the relationship, is limited. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…This seasonal decline in ET was dominated by a corresponding decline in T (Figure 7a), whereas E was largely aseasonal across the measurement period (Figure 6a) with little difference among ecosystem types in its cumulative sum (Figure 6b) despite different responses to wet conditions that were related to soil texture. The cumulative sum of T across the measurement period differed little among forests as anticipated (Figure 7b), despite differences in forest composition (Butterworth et al, 2021;Murphy et al, 2022), and wetlands supported less cumulative T (Figure 7b). We describe the FVS partitioning outcomes that resulted in these findings before describing seasonal patterns of fluxes and their responses to micrometeorological variability across different ecosystems.…”
Section: Overviewsupporting
confidence: 62%
“…This seasonal decline in ET was dominated by a corresponding decline in T (Figure 7a), whereas E was largely aseasonal across the measurement period (Figure 6a) with little difference among ecosystem types in its cumulative sum (Figure 6b) despite different responses to wet conditions that were related to soil texture. The cumulative sum of T across the measurement period differed little among forests as anticipated (Figure 7b), despite differences in forest composition (Butterworth et al, 2021;Murphy et al, 2022), and wetlands supported less cumulative T (Figure 7b). We describe the FVS partitioning outcomes that resulted in these findings before describing seasonal patterns of fluxes and their responses to micrometeorological variability across different ecosystems.…”
Section: Overviewsupporting
confidence: 62%
“…These sites sample a broader range of forests, wetlands, and lakes in the landscape that contributed to the scaling goals of the CHEESEHEAD19 study (Butterworth et al, 2021), and included recent clear-cuts to older established forests. Site descriptions are provided at http://cheesehead19.org with further details in Butterworth et al (2021), Murphy et al (2022), andDesai et al (2021) and in the official data repository.…”
Section: Flux Tower Sitesmentioning
confidence: 99%
“…Aggregation of CO 2 fluxes from a collection of sites in and around the Chequamegon‐Nicolet National Forest in the summers of 2002 and 2003 demonstrated that footprint‐weighted NEE, R eco , and GPP at the tall tower were within 11% of the combined fluxes from 13 surrounding towers (Desai, Noormets, et al., 2008 ). Forest structure and age distribution strongly impact these fluxes, reflecting the history of land management and canopy complexity on modulating regional carbon cycle responses in forests (Desai et al., 2005 , 2007 ; Murphy et al., 2022 ). Wetlands and other aquatic landscapes (lakes, rivers, and ponds) form more than a quarter of the landscape and have been shown to have unique responses to hydrologic change (Buffam et al., 2011 ; Gorsky et al., 2021 ; Pugh et al., 2018 ; Turner et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Land-atmosphere field experiments have continued to provide insight on scaling through advances in observing capability as noted in several papers in this collection. For example, from CHEESEHEAD19, Murphy et al (2022) find canopy structural metrics do not linearly scale with spatial resolution, which influences how those metrics link to ecosystem functions through water-use and light-use efficiencies. Meanwhile, with a range of atmospheric profilers and surface radiation observations, Sedlar et al (2022) show how atmospheric boundary layer development is influenced by scales of cloud regimes and its imprint on turbulent fluxes.…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…For example, from CHEESEHEAD19, Murphy et al. (2022) find canopy structural metrics do not linearly scale with spatial resolution, which influences how those metrics link to ecosystem functions through water‐use and light‐use efficiencies. Meanwhile, with a range of atmospheric profilers and surface radiation observations, Sedlar et al.…”
Section: A Scale For All Silosmentioning
confidence: 99%